2022
DOI: 10.1007/s12072-022-10424-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysfunction-associated fatty liver disease and liver function markers are associated with Crohn’s disease but not Ulcerative Colitis: a prospective cohort study

Abstract: Background Metabolic dysfunction-associated fatty liver disease (MAFLD) is recently recognized as a condition featured with metabolic dysfunctions in liver. It has been supposed that MAFLD might contribute to the development of IBD, but evidence from prospective cohort studies is lacking and inconclusive. Methods A total of 221,546 females and 183,867 males from the UK Biobank cohort enrolled in 2006–2010 were included to examine whether MAFLD and liver fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Some studies suggest that IBD-induced NAFLD can further aggravate the severity of IBD and increase the risk of hepatocellular carcinoma (HCC) ( 32 34 ). An epidemiology study found that people with metabolic dysfunction associated fatty liver (MAFLD) have a 12% increased risk of IBD ( 35 ). Metabolic syndrome, characterized by metabolic disorders, plays a major role in this ( 36 ), with IL-17 a key factor in the clinical manifestations of metabolic syndrome ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that IBD-induced NAFLD can further aggravate the severity of IBD and increase the risk of hepatocellular carcinoma (HCC) ( 32 34 ). An epidemiology study found that people with metabolic dysfunction associated fatty liver (MAFLD) have a 12% increased risk of IBD ( 35 ). Metabolic syndrome, characterized by metabolic disorders, plays a major role in this ( 36 ), with IL-17 a key factor in the clinical manifestations of metabolic syndrome ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…A low serum SHBG level has been observed as an inflammatory marker ( 53 ), suggesting a protective role of SHBG in metabolic and inflammatory diseases. Metabolic dysregulation has been implicated in the pathogenesis of IBD ( 54 ), with patients with metabolic dysfunction-associated fatty liver disease having a higher risk of developing CD ( 55 ). These findings supported the protective role of SHBG that we have identified in the development of CD.…”
Section: Discussionmentioning
confidence: 99%
“…4 Hepatic steatosis is also associated with the development of cardiovascular events, and previous cohort studies have shown that the incidence of cardiovascular events increases with the development of liver fibrosis. 5,6 Risk factors for hepatic steatosis include type 2 diabetes, obesity and ageing. While there are no US Food and Drug Administration-approved oral glucose-lowering drugs for hepatic steatosis, pioglitazone, 7 glucagon-like peptide-1 (GLP-1) receptor agonists 8,9 and sodium glucose cotransporter 2 (SGLT2) inhibitors 10 have been reported to improve hepatic steatosis in clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The progression of MASLD to metabolic steatohepatitis (MASH) increases the risk of liver‐related mortality because of fibrosis of the liver 4 . Hepatic steatosis is also associated with the development of cardiovascular events, and previous cohort studies have shown that the incidence of cardiovascular events increases with the development of liver fibrosis 5,6 . Risk factors for hepatic steatosis include type 2 diabetes, obesity and ageing.…”
Section: Introductionmentioning
confidence: 99%